Analisis Pemeriksaan Pajak dalam Rangka Optimalisasi Penerimaan Negara di Sektor Perpajakan - Bambang Irawan; Teguh Budiono (Institut Ilmu Sosial dan Manajemen STIAMI, 2015)
The purpose of this study was to determine how the tax audit can optimize revenues in the tax sector, factors that become an obstacle in carrying out tax audits, and any solution that could be recommended to overcome such obstacles. This study used a qualitative approach, by conducting interviews, observation and document study. The informants in this study are stakeholders who understand the implementation of a tax audit as many as six informants. Tax audits to optimize state income in the taxation sector is influenced by several factors, namely legislation which provides clarity, certainty and simplicity that can reduce the dispute regulations, government policy in implementing regulations, administrative system that provides counseling function, care and supervision as well information systems support, excellent service in the implementation of a tax audit, the level of awareness and understanding of the taxpayer to the tax laws, and functional Examiner and professional integrity. There are several obstacles to the implementation of the tax audit, include unrealistic state revenue target in the taxation sector, tax laws have multiple interpretations, limited external data and unintegrated internal data held, the burden of routine inspections are high, the lack of quantity and quality Functional Tax Audit, and lack of official vehicles and operating funds. Solutions to overcome these obstacles, include preparation of the revenue target should be more realistic, tax laws should be drawn with regard to principles of clarity, certainty and simplicity, optimization of Government Regulation No. 31 of 2012, reducing routine inspection, addition of the quantity and quality Functional Tax Audit, and the provision of vehicles service.